Cyclic Effective Pressure Loading Impacts Glacial Slip Over Deformable Beds - N. Morgan‐Witts; D. D. Hansen; L. K. Zoet; M. Haseloff (Geophysical Research Letters)
Abstract Tidal fluctuations at the grounding zones of marine‐terminating glaciers induce oscillations in effective pressure at the glacier bed, altering ice‐till coupling and glacial slip. Glaciers slipping atop deformable beds with oscillatory pressure fluctuations can generate a transient porewater pressure feedback within the underlying till, affecting bed coupling and the yield stress of the till. The influence of this transient feedback can range from negligible to dominating glacier slip; however, little is known about the governing mechanics. We used a cryogenic ring shear device to simulate basal slip under oscillating pressure conditions with varying amplitudes to directly measure drag under transient forcing. We find a path dependence (hysteresis) within the shear stress–effective pressure relationship and a greater extent of deformation within till undergoing cyclic loading compared to static loading. Importantly, shear stress is greater when effective pressure is unloading, indicating potential stabilizing feedbacks during rising tides or anomalous fluid pressure spikes.